Endocrine Pathology: Differential Diagnosis and Molecular Advances - Lloyd, Ricardo V.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Endocrine Pathology: Differential Diagnosis and Molecular Advances, Second Edition provides detailed coverage of endocrine pathology with extensive discussion of the differential diagnosis as well as presentation of molecular pathobiology of the major endocrine organs. Revised and expanded from the first edition, each chapter, written by leaders in their respective field, has been updated with the latest advances that are transforming the field of endocrine pathology. Richly illustrated with color photomicrographs, useful diagrams and line drawings, each chapter includes differential diagnosis of common and uncommon lesions as well as material on molecular developments, with emphasis on the molecular findings that are most helpful in the diagnosis of specific disorders. Endocrine Pathology: Differential Diagnosis and Molecular Advances, Second Edition, provides a useful and well-organized resource designed not only for the endocrine pathologist and the general surgical pathologist, but also for the clinical endocrinologist and the endocrine surgeon.
Methods in Cellular and Molecular Pathology -- Hypothalamus and Neurohypophysis -- Tumors in the Adenohypophysis -- Recent Developments in Molecular Embryogenesis and Molecular Biology of the Pituitary -- Recent Developments in the Molecular Biology of Pituitary Tumors -- The Pineal Gland -- The Parathyroid -- Recent Developments in the Molecular Biology of the Parathyroid -- Pathology of Thyroid Gland -- Recent Developments in the Molecular Biology of the Thyroid -- Adrenal Cortex -- Adrenal Medulla and Paraganglia -- Molecular Biology of Pheochromocytomas and Paragangliomas -- Endocrine Ovaries -- Endocrine Testis -- Endocrine Tumors of the Gastrointestinal System -- The Endocrine Pancreas -- Neuroendocrine Differentiation Patterns in Various Organs (Including Lung, Breast, Skin and Urogenital Tract) -- Endocrine Lung -- Cutaneous Neuroendocrine Tumors -- Neuroendocrine Carcinomas of the Thymus -- Endocrine Placenta -- Fine Needle Aspiration Cytology of Endocrine Glands -- Multiple Endocrine Neoplasia Syndrome -- Polyglandular Autoimmune Diseases -- Biochemical Testing for Neuroendocrine Tumors -- Surgical Management of Endocrine Disorders -- Medical Treatment of Neuroendocrine Tumors -- Radiation Treatment of Endocrine Tumors -- Future Directions in Endocrine Pathology.
Keywords: Medicine; Medical laboratories; Endocrinology; Pathology; Medicine & Public Health; Pathology; Endocrinology; Laboratory Medicine